A method for integrated production of a bifunctional skin silicone foam composite and applications

CN122427406BActive Publication Date: 2026-10-13GUANGDONG DINGLISEN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610634664.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-09
Publication Date
2026-10-13
Estimated Expiration
2046-05-09

AI Technical Summary

Technical Problem

该工艺存在以下缺陷:(1)界面结合薄弱:功能层与已固化基体形成 “二次界面”,依赖物理吸附与弱作用力结合,湿热老化、反复摩擦与压缩后易出现起翘、脱落、渗漏

Benefits of technology

[0023]1. 本发明通过设计耐磨涂层的组合物,使其表干后仍含有未反应乙烯基活性基团,并在发泡混合料的B组分中引入含氢交联剂、在A组分中引入铂金催化剂,在热硫化过程中耐磨涂层表面的乙烯基与泡沫基体中的硅氢键发生原位加成反应,实现耐磨层与聚硅氧烷泡沫层的化学键合一体化;同时,底涂层中含有硅烷偶联剂、MQ树脂及铂金催化剂,在硫化过程中与泡沫层形成界面增强结合,从而实现了功能层与聚硅氧烷泡沫基体在分子网络层面的本质融合,极大提升了产品一致性及界面可靠性,避免使用过程中层间脱落的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an integrated preparation method of a double-functional surface layer polysiloxane foam composite material, which is prepared through the cooperation design of an upper transfer film, a lower release film and a foaming mixture, and is simultaneously formed and chemically bonded in situ between layers through a single thermal vulcanization process, so that the double functions of upper wear resistance and lower adhesion are integrated. The upper transfer film contains vinyl-terminated linear polysiloxane, acrylate-modified MQ silicone resin, inorganic wear-resistant filler and platinum catalyst; the lower release film is coated with silicone pressure-sensitive adhesive; and the foaming mixture is compounded from vinyl-terminated linear polysiloxane, branched polysiloxane, polysiloxane resin and hydrogen-containing crosslinking agent. After thermal vulcanization, the base material is peeled off, and the integrated composite material is prepared through secondary vulcanization. The application eliminates the secondary interface from the source, and the interface is firm, wear-resistant and excellent in adhesion, has low compression permanent deformation, good waterproof sealing performance, and the process is simple and efficient, so that the foam composite material can be used in the fields of consumer electronics, new energy vehicles and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic polymer materials, and in particular to an integrated preparation method and application of a bifunctional surface polysiloxane foam composite material based on a PET substrate. Background Technology

[0002] Polysiloxane foam materials combine high elasticity, wide temperature range stability, weather resistance, and electrical insulation, making them widely used in cushioning, sealing, and shock-absorbing structural components for consumer electronics, new energy vehicles, and smart wearable devices. As products become thinner and more integrated, there are increasing demands on foam materials to meet dual functional and performance requirements: surface wear resistance, substrate-side adhesion, strong interface, and long-term service reliability.

[0003] There are two ways to improve the wear resistance of existing polysiloxane foam materials. There are two main ways to apply wear-resistant coatings. The first is to add wear-resistant fillers during the foaming process so that the wear-resistant fillers are evenly distributed throughout the foamed material. Only a very small number are located on the surface of the material, and the vast majority are wrapped inside the foam cells and cannot play a wear-resistant role. The surface wear resistance is limited. The second is the post-processing coating process, that is, the foam matrix is ​​vulcanized and molded first, and then the wear-resistant layer and adhesive layer are applied by spraying, scraping, bonding and other methods. This process has the following defects: (1) Weak interface bonding: The functional layer and the cured matrix form a "secondary interface", which relies on physical adsorption and weak force bonding. After damp heat aging, repeated friction and compression, it is easy to lift, fall off and leak. (2) Poor coating uniformity: The surface of the foamed matrix is ​​porous and has low strength. Spraying and scraping can easily cause the coating to penetrate into the pores, resulting in uneven thickness and edge accumulation, making it difficult to form a continuous and dense wear-resistant layer.

[0004] In addition, in practical applications, in order to simplify the assembly process and improve structural reliability, polysiloxane foam composite materials, while achieving surface wear resistance, usually need to be used in combination with PET substrate and pressure-sensitive adhesive layer to achieve rapid bonding and stable adhesion to the device surface.

[0005] Therefore, there is an urgent need to develop an integrated preparation method for bifunctional surface polysiloxane foam composite materials to solve the technical problems that urgently need to be addressed in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the primary objective of this invention is to provide an integrated preparation method for a dual-functional surface polysiloxane foam composite material. Through the synergistic design of the wear-resistant coating, PET composite substrate, and foaming mixture, foaming and molding are simultaneously achieved in a single hot vulcanization process. The layers are integrated through bonding, eliminating interfaces at the source and achieving dual-functional integration of "wear-resistant upper layer and adhesive lower layer".

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] An integrated preparation method for a bifunctional surface-layered polysiloxane foam composite material includes the following steps:

[0009] (1) Preparation of upper transfer film: A wear-resistant coating composition is coated on a first substrate and then cured to obtain a surface-dried wear-resistant coating. The wear-resistant coating composition includes 5-60 parts of acrylate-modified MQ silicone resin, 10-30 parts of vinyl-terminated linear polysiloxane, 2-10 parts of hydrogen-containing crosslinking agent, 5-30 parts of inorganic wear-resistant filler, 1-10 parts of silane coupling agent, 80-120 parts of first diluent, 0.2-2 parts of adhesion promoter, 0.5-2 parts of platinum catalyst and 0.5-2 parts of inhibitor; the surface of the surface-dried wear-resistant coating still retains unreacted vinyl active groups.

[0010] (2) Preparation of the lower composite film: A base coating is applied to one side of the PET substrate, and a pressure-sensitive adhesive layer is provided on the other side; the base coating contains 5-15 parts of silane coupling agent, 10-25 parts of MQ resin, 1-3 parts of zinc stearate, 0.1-0.5 parts of platinum catalyst, 0.1-0.5 parts of inhibitor and 40-80 parts of ethanol, which are used to enhance the interfacial bonding force between the polysiloxane foam layer and the PET substrate.

[0011] (3) Preparation of foamed mixture: Mix component A and component B at a mass ratio of 1:1 to obtain foamed mixture. Component A includes vinyl-terminated linear polysiloxane, platinum catalyst, second diluent and reinforcing filler; component B includes branched polysiloxane, polysiloxane resin, hydrogen-containing crosslinking agent and inhibitor.

[0012] (4) Mix the foaming materials of components A and B, apply them to the surface of the base coating, and then cover the wear-resistant coating side of the upper transfer film onto the foaming mixture. Heat vulcanize at 100-130 °C for 8-15 minutes. The foaming mixture cross-links and foams to form a polysiloxane foam matrix. At the same time, the wear-resistant coating, the polysiloxane foam matrix, and the base coating are integrated by in-situ chemical bonding.

[0013] (5) Peel off the first substrate to transfer the wear-resistant coating to the polysiloxane foam matrix, and then perform secondary vulcanization at 140-200 °C for 10-30 minutes to obtain the composite material.

[0014] As a preferred technical solution, component A comprises 50-80 parts of vinyl-terminated linear polysiloxane, 0.1-1.0 parts of platinum catalyst, 5-20 parts of second diluent, and 10-40 parts of reinforcing filler; component B comprises 20-60 parts of branched polysiloxane, 20-60 parts of polysiloxane resin, 1.0-2.6 parts of hydrogen-containing crosslinking agent, 0.1-1.0 parts of inhibitor, and 1-10 parts of foaming agent.

[0015] As a preferred technical solution, the vinyl-terminated linear polysiloxane has a molecular weight of 50,000 to 250,000 and a vinyl content of 0.05 to 0.30 mol.

[0016] As a preferred technical solution, the branched polysiloxane in component B has the following general formula: (R3) 1 SiO 1 / 2 ) a (R2 2 SiO 2 / 2 ) b (R1 3 SiO 3 / 2 ) c (SiO 4 / 2 ) d , where R 1-3 It is a C1-C6 alkyl, vinyl, or aryl group, and the molecule contains at least two vinyl groups, a+b+c+d=1, and c>0.05.

[0017] As a preferred technical solution, the polysiloxane resin in component B is an organopolysiloxane resin containing M, T and Q structural units; its weight-average molecular weight is 5000 to 50000.

[0018] As a preferred technical solution, the foaming agent is selected from at least one of sodium bicarbonate, low-temperature activated azodicarbonamide, or sulfonyl hydrazine.

[0019] As a preferred technical solution, the interfacial release force between the wear-resistant coating and the first substrate is 40-300g / 25mm.

[0020] In view of the shortcomings of the prior art, the second objective of the present invention is to provide an application of a dual-functional surface polysiloxane foam composite material.

[0021] Application of a dual-functional surface polysiloxane foam composite material as a buffer, shock absorber or sealing component inside electronic devices.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. This invention designs a wear-resistant coating composition that retains unreacted vinyl active groups even after surface drying. A hydrogen-containing crosslinking agent is introduced into component B of the foaming mixture, and a platinum catalyst is introduced into component A. During thermal vulcanization, the vinyl groups on the wear-resistant coating surface undergo in-situ addition reactions with the silane-hydrogen bonds in the foam matrix, achieving chemical bonding between the wear-resistant layer and the polysiloxane foam layer. Simultaneously, the undercoat contains a silane coupling agent, MQ resin, and a platinum catalyst, which form an interface-enhanced bond with the foam layer during vulcanization. This achieves a fundamental fusion of the functional layer and the polysiloxane foam matrix at the molecular network level, greatly improving product consistency and interface reliability, and preventing interlayer delamination during use.

[0024] 2. In the polysiloxane foam matrix of the foamed mixture, the vinyl-terminated linear polysiloxanes, branched polysiloxanes, and hydrogen-containing crosslinking agents work synergistically to form a three-dimensional crosslinked network structure within the material, resulting in excellent overall resilience and mechanical properties. The acrylate-modified MQ silicone resin in the wear-resistant coating not only adjusts the release force at the interface with the first substrate, ensuring controllable peeling of the wear-resistant coating, but also further improves the coating's hardness and wear resistance, significantly enhancing the product's interface reliability, structural integrity, and surface functional stability.

[0025] 3. In this invention, one side of the PET substrate is firmly connected to the polysiloxane foam matrix through the base coating, and the other side of the PET substrate forms a stable application interface structure with the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer can be directly bonded to the surface of electronic devices, simplifying the assembly process of composite materials. At the same time, after the transfer film is peeled off, the PET substrate serves as the bottom support of the composite material, ensuring the overall mechanical stability. Detailed Implementation

[0026] The following examples further illustrate the features of the present invention and other related features in detail, so as to facilitate understanding by those skilled in the art.

[0027] Embodiments of the present invention provide an integrated preparation method for a bifunctional surface-layered polysiloxane foam composite material, comprising the following steps:

[0028] (1) Preparation of the upper transfer film: A wear-resistant coating composition is coated on a first substrate. The wear-resistant coating composition includes 5-60 parts of acrylate-modified MQ silicone resin, 10-30 parts of vinyl-terminated linear polysiloxane, 2-10 parts of hydrogen-containing crosslinking agent, 5-30 parts of inorganic wear-resistant filler, 1-10 parts of silane coupling agent, 80-120 parts of first diluent, 0.2-2 parts of adhesion promoter, 0.5-2 parts of platinum catalyst, and 0.5-2 parts of inhibitor. Then, it is cured to obtain a surface-dried wear-resistant coating. The surface of the surface-dried wear-resistant coating still retains unreacted vinyl active groups, which are used for subsequent in-situ chemical bonding with the foam matrix. The inorganic wear-resistant filler can be uniformly dispersed in the coating composition under the action of the silane coupling agent. The first diluent is used to adjust the fluidity of the coating composition so that it has suitable fluidity to spread evenly on the first substrate.

[0029] (2) Preparation of the composite film: A primer coating is applied to one side of the PET substrate, and a pressure-sensitive adhesive layer is applied to the other side; a composite structure of "primer coating / PET substrate / pressure-sensitive adhesive layer" is formed, wherein the primer coating is used to enhance the interfacial bonding with the subsequent foam layer. The primer coating contains 5-15 parts of silane coupling agent, 10-25 parts of MQ resin, 1-3 parts of zinc stearate, 0.1-0.5 parts of platinum catalyst, 0.1-0.5 parts of inhibitor and 40-80 parts of ethanol, which are used to enhance the interfacial bonding between the polysiloxane foam layer and the PET substrate.

[0030] (3) Preparation of foamed mixture: Mix component A and component B at a mass ratio of 1:1 to obtain foamed mixture. Component A includes vinyl-terminated linear polysiloxane, platinum catalyst, second diluent and reinforcing filler; component B includes branched polysiloxane, polysiloxane resin, hydrogen-containing crosslinking agent and inhibitor.

[0031] (4) Mix the foaming materials of components A and B and apply them to the surface of the base coating. Then, cover the wear-resistant coating side of the upper transfer film onto the foaming mixture. Under the action of the catalyst and foaming agent, heat-curing is carried out at 100-130 °C for 8-15 minutes. Most of the vinyl-terminated linear polysiloxanes in the foaming mixture undergo cross-linking reaction with the hydrogen-containing cross-linking agent to form a three-dimensional cross-linked network structure of polysiloxane foam matrix, which makes the material as a whole have excellent resilience and mechanical properties. Simultaneously, the wear-resistant coating and the silicone-containing undercoat of the lower composite film bond with the vinyl-terminated linear polysiloxane, branched polysiloxane, and polysiloxane resin in the foaming mixture, respectively. The remaining vinyl active groups of the surface-dried upper transfer film not only further crosslink with the hydrogen-containing crosslinking agent of the wear-resistant coating composition, but also partially crosslink with the vinyl active groups and hydrogen-containing crosslinking agents of the wear-resistant coating composition and the foaming mixture, thereby achieving an integrated bonding of the upper and lower interfaces: the upper surface of the foam material is bonded to the wear-resistant coating, the lower surface is bonded to the undercoat, and it is firmly bonded to the PET substrate with pressure-sensitive adhesive, forming an integrally bonded foam composite material.

[0032] (5) Peel off the first substrate to transfer the wear-resistant coating to the polysiloxane foam matrix, and then perform secondary vulcanization at 140-200 °C for 10-30 minutes to achieve deep cross-linking, structural shaping and removal of small molecules in the composite material, thereby improving structural stability.

[0033] In some examples, component A comprises 50-80 parts of vinyl-terminated linear polysiloxane, 0.1-1.0 parts of platinum catalyst, 5-20 parts of second diluent, and 10-40 parts of reinforcing filler; component B comprises 20-60 parts of branched polysiloxane, 20-60 parts of polysiloxane resin, 1.0-2.6 parts of hydrogen-containing crosslinking agent, 0.1-1.0 parts of inhibitor, and 1-10 parts of foaming agent.

[0034] In some examples, the vinyl-terminated linear polysiloxane has a molecular weight of 50,000–250,000 and a suitable molecular chain length, which can form a flexible and relatively strong molecular chain network after crosslinking and curing. This provides excellent elastic recovery of the foam matrix and reduces permanent deformation after long-term compression. The vinyl content is 0.05–0.30 mol%, and not less than 0.05 mol%, ensuring sufficient reactive sites for bonding with the branched polysiloxane, complete hydrosilylation reaction, and wear-resistant coating and silicon-containing undercoat, achieving complete crosslinking and curing. This avoids problems such as low mechanical strength, poor heat resistance, and poor aging resistance of the foam matrix due to insufficient crosslinking. The vinyl content is not higher than 0.30 mol%, preventing excessively high crosslinking density, overly dense molecular chain network, excessively high foam hardness, and decreased elasticity. It also avoids uneven cell structure and localized bursting caused by a mismatch between the crosslinking reaction rate and the gas production rate of the blowing agent.

[0035] In some examples, the branched polysiloxane in component B has the following general formula: (R3) 1 SiO 1 / 2 ) a (R2 2 SiO 2 / 2 ) b (R1 3 SiO 3 / 2 ) c (SiO 4 / 2 ) d , where R 1-3 It is a C1-C6 alkyl, vinyl, or aryl group, and the molecule contains at least two vinyl groups, a+b+c+d=1, and c>0.05. Vinyl groups can undergo addition reactions with linear polysiloxanes to form a network structure, further improving the tear strength of the polysiloxane foam matrix.

[0036] In some examples, the foaming agent is selected from at least one of sodium bicarbonate, low-temperature activated azodicarbonamide, or sulfonyl hydrazine. Within the thermal vulcanization range of 100-130 °C, this type of foaming agent can stably decompose to produce inert gases such as CO2 and N2, providing a stable, sufficient, and uniform nucleation gas source for the foam, making the foaming ratio stable and controllable, and avoiding problems such as low foaming ratio, hard foam, and poor buffering caused by insufficient reaction by-product gas.

[0037] Acrylic-modified MQ silicone resin has low surface energy, strong lubricity, and weak adhesion to the substrate. As its dosage increases, the overall surface energy of the wear-resistant coating decreases, weakening its adhesion to the first substrate and consequently reducing the interfacial release force. By adjusting the dosage of acrylate-modified MQ silicone resin within the above range, the interfacial release force between the wear-resistant coating and the first substrate can be maintained at 40-300 g / 25mm.

[0038] In some examples, the first diluent is a low-viscosity linear polydimethylsiloxane or at least one of toluene, xylene, ethyl acetate, and isopropanol, used to adjust the flowability of the abrasion-resistant coating composition so that it can be spread evenly on the first substrate.

[0039] In some examples, the second diluent is a low-viscosity linear polydimethylsiloxane or at least one of toluene, xylene, ethyl acetate, and isopropanol, used to reduce the viscosity of component A so that the components are uniformly dispersed.

[0040] In some examples, the reinforcing filler is at least one of fumed silica, nano-calcium carbonate, and fumed alumina. The reinforcing filler is dispersed in a polysiloxane system, which effectively improves the mechanical strength, tear strength, and dimensional stability of the foam matrix.

[0041] The adhesion promoter is used to increase the adhesion between the first substrate and the abrasion-resistant coating, and typically includes a silane coupling agent and other substances in combination. In some examples, the adhesion promoter may be Dow Corning 297, Dow Corning 397, or Dow Corning 9167.

[0042] In some examples, the hydrogen-containing crosslinking is an organopolysiloxane having hydrogen atoms bonded to silicon, wherein the mass fraction of hydrogen atoms in the organopolysiloxane is 0.5% to 2%.

[0043] In some examples, the inhibitor is one or two of diethyl maleate, 3-buten-1-yn-1-ylbenzene, and cyclohexynol.

[0044] In some examples, the first substrate can be a PET film, a BOPP film, or a PE film.

[0045] The embodiments of the present invention provide an application of a dual-functional surface polysiloxane foam composite material, which can be directly bonded to the inside of electronic devices through its pressure-sensitive adhesive layer, and used as a buffer, shock absorber or sealing component.

[0046] Example 1

[0047] Example 1 of the present invention provides a bifunctional surface-layered polysiloxane foam composite material, which is prepared according to the following steps:

[0048] (1) Preparation of the upper transfer film: 100 parts of ethyl acetate, 60 parts of acrylate-modified MQ silicone resin, 15 parts of vinyl-terminated linear polysiloxane, 5 parts of hydrogen-containing crosslinking agent, 20 parts of nano-silica, 5 parts of silane coupling agent KH-560, 1 part of Dow Corning 297 (adhesion enhancer), 2 parts of platinum catalyst (platinum content approximately 3000 ppm) and 1 part of inhibitor were mixed evenly and coated uniformly onto a 50 μm thick PET substrate. The mixture was then cured at 120 °C for 2 minutes to form a transferable and wear-resistant coating. The release force between the obtained upper transfer film and the PET substrate was approximately 120 g / 25 mm.

[0049] (2) Preparation of the lower release film: A base coating is applied to one side of the PET substrate, and a pressure-sensitive adhesive layer is provided on the other side; the base coating contains 10 parts of KH-560, 15 parts of MQ resin, 2 parts of zinc stearate, 0.2 parts of platinum catalyst, 0.1 parts of inhibitor and 50 parts of ethanol.

[0050] (3) Preparation of Component A: In a planetary mixer, add 70 parts by mass of vinyl-terminated linear polydimethylsiloxane (weight average molecular weight 100,000, vinyl content 0.15 mol%), 30 parts by mass of fumed silica (specific surface area 300 m² / g), 15 parts by mass of dimethyl silicone oil (100 mPa·s), and 0.5 parts by mass of platinum catalyst (Pt content 3000 ppm). Stir at high speed under vacuum and degas to obtain Component A.

[0051] (4) Preparation of component B: 40 parts of branched polysiloxane (degree of polymerization n=1500), 50 parts of MQ type organopolysiloxane resin (weight average molecular weight of 15,000), 1.8 parts of hydrogen-containing silicone oil crosslinking agent (hydrogen mass fraction of 1.6%), 5.0 parts of low-temperature activated azodicarbonamide foaming agent and 0.3 parts of ethynylcyclohexanol inhibitor were added sequentially to a planetary mixer; the mixture was stirred at high speed under vacuum and degassed to obtain component B.

[0052] (4) Mix component A and component B in a high-speed mixer at a mass ratio of 1:1 to obtain a foamed mixture. Coat the foamed mixture on the surface of the silicone-containing base coating of the lower PET substrate. Then cover the foamed mixture with the wear-resistant coating side of the upper transfer film. Heat vulcanize at 120 °C for 10 minutes.

[0053] (5) After cooling to room temperature, peel off and remove the PET carrier of the upper transfer film to transfer the wear-resistant coating to the upper surface layer of the foam matrix. Then place it in an oven at 180°C for a second vulcanization for 20 minutes to obtain the composite material of Example 1.

[0054] Example 2

[0055] The difference between the composite material of Example 2 and that of Example 1 is as follows: (1) Preparation of the upper transfer film: 80 parts of ethyl acetate, 60 parts of acrylate-modified MQ silicone resin, 15 parts of vinyl-terminated linear polysiloxane, 5 parts of hydrogen-containing crosslinking agent, 20 parts of nano silica, 4 parts of silane coupling agent KH-560, 1 part of Dow Corning 297 (adhesion aid), 2 parts of platinum catalyst (platinum content of about 3000 ppm) and 1 part of inhibitor were mixed evenly and coated evenly on a 50 μm thick PET substrate. The mixture was cured at 120 °C for 2 minutes to form a transferable and wear-resistant coating. In the obtained upper transfer film, the release force between the coating and the PET substrate was about 80 g / 25 mm. (2) The first hot vulcanization conditions of the foamed mixture were adjusted to 115 °C for 15 minutes. The remaining process steps were the same as in Example 1, and the composite material of Example 2 was obtained.

[0056] Example 3

[0057] The difference between the composite material of Example 3 and Example 1 is that: (1) the vinyl-terminated linear polysiloxane in component A is adjusted to 60 parts and the fumed silica is adjusted to 25 parts; the branched polysiloxane in component B is adjusted to 45 parts and the amount of MQ silicone resin is adjusted to 35 parts; the rest of the preparation process is the same as that of Example 1, and the composite material of Example 3 is obtained.

[0058] Comparative Example 1

[0059] The difference between the composite material of Comparative Example 1 and Example 1 is that: Comparative Example 1 directly coats the foaming mixture onto the PET substrate without covering it with any transfer film or base coating with wear-resistant coating, performs hot vulcanization, peels off the release film, and obtains a pure foam material without a functional layer.

[0060] Comparative Example 2

[0061] The difference between the composite material of Comparative Example 2 and Example 1 is that the upper transfer film of Comparative Example 2 remains unchanged, but the lower composite film is replaced with a PET substrate without a bottom coating. The composite material of Comparative Example 2 is obtained by curing it in an oven at 120 °C for 20 min.

[0062] Comparative Example 3

[0063] Take the pure foam material obtained from Comparative Example 1 and perform post-processing: after pre-treating its upper surface, spray it with polyacrylate containing nano silica (20% by mass of nano silica), and cure it at 130°C for 25 minutes to form a wear-resistant coating.

[0064] Performance testing:

[0065] 1. Foaming ratio: Measure the density of the foamed mixture before vulcanization and the foam material after vulcanization, and calculate the foaming ratio by comparing it with the specific gravity of the mixture before foaming.

[0066] 2. Compression set test: The material is compressed to 50% of its original thickness at 70℃, kept for 22 hours, removed, and allowed to recover at room temperature (25±2℃) for 30 minutes. The thickness change is measured and the deformation rate is calculated.

[0067] 3. Adhesion Test: All samples were boiled in 100 ℃ water for 4 hours, removed and dried, and then conditioned in a standard environment (25±2℃, 50±5% RH) for 2 hours. The manual peeling method was used for evaluation: a peeling force was applied to the interface between the foam material and the pressure-sensitive adhesive using a scraper, and the failure mode and ease of peeling were observed and recorded.

[0068] 4. Scratch Resistance: Using a hemispherical stainless steel probe with a radius of 0.5 mm, a vertical load of 0.49 N (50 g) is applied, and the sample surface is scratched unidirectionally at a speed of 100 mm / min. After the test, the coating at the scratched area is observed with a magnifying glass to see if there are visible cracks, peeling, or flaking. Good scratch resistance: No scratches on the coating. Moderate scratch resistance: Minor scratches on the coating. Poor scratch resistance: Significant damage in multiple places on the coating.

[0069] 5. Test the waterproof sealing performance of the material using a sealing test fixture: The sealing test fixture has a 30mm diameter opening in the center. Cut the sample into a 50mm × 50mm square, place it in the self-made sealing test fixture, and press it firmly. Apply a hydrostatic pressure of 0.05MPa to the upper surface of the material at the opening and maintain it for 30 minutes. Observe whether there is water leakage on the lower surface of the material. Interface leakage: Water droplets or continuous water marks appear on the outer ring of the sealing interface.

[0070] Table 1 shows the performance test results of Examples 1-3 and Comparative Examples 1-3.

[0071]

[0072] As shown in Table 1, the test results of all examples and comparative examples show that the materials were damaged after boiling and aging, especially the interfacial bonding structure between the wear-resistant coating, the foam matrix, and the PET layer with the primer. After boiling and aging, the layers were peeled off, and the materials of Examples 1-3 were completely destroyed during the peeling process. This indicates that through the integrated hot vulcanization process of the present invention, the foam matrix forms a continuous and dense interface with the wear-resistant coating and the primer through a cross-linking network and / or chemical bonds. The integration with the foam matrix makes it difficult for the composite material to experience interlayer peeling or detachment during long-term use, significantly improving interface reliability and service life. In contrast, Comparative Example 1, due to the lack of a functional layer, has poor scratch resistance and waterproof sealing, resulting in interface leakage; Comparative Example 2, using a PET substrate without a primer, showed significant interface detachment after boiling; Comparative Example 3, using a secondary interface formed by a step-by-step post-processing process, showed further degradation in adhesion after boiling and aging, leading to the peeling of the foam matrix from the coating. This indicates that the composite material formed by the integrated hot vulcanization process is more reliable than those without a functional layer, without a primer, or with a secondary interface formed by step-by-step processing.

[0073] The compression set of Example 3 was significantly lower than that of the comparative samples. This indicates that, through the synergistic effect of branched polysiloxane and MQ-type organopolysiloxane resin, a highly elastic, creep-resistant three-dimensional cross-linked network was formed within the polysiloxane foam matrix, resulting in superior elastic recovery performance. Example 3, while achieving a higher foaming ratio, still maintained excellent deformation resistance comparable to conventional foams, demonstrating that by adjusting the proportions of each raw material within the foaming mixture formulation range of this invention, materials possessing both good resilience and compressive strength can be obtained.

[0074] The integrated preparation method of this invention simultaneously achieves multifunctional integration of "wear-resistant upper layer and adhesive lower layer" in a single hot vulcanization process. Waterproof sealing test results show that samples in Examples 1-3, due to their integrated silicon-containing undercoating chemically bonded to the foam matrix on their lower surface, can form a complete and reliable sealing interface with the sealing test fixture, maintaining a leak-free seal for 30 minutes under 0.05 MPa hydrostatic pressure. In contrast, Comparative Example 1, lacking an adhesive functional layer, has a direct contact between the foam matrix and the fixture at the sealing interface, resulting in significant interface leakage. The adhesive layers in Comparative Examples 2 and 3 have weak adhesion to the foam matrix, easily peeling off under hydrostatic pressure, also exhibiting leakage. These results confirm the fundamental advantage of integrated chemical bonding in achieving immediate and reliable sealing.

[0075] In summary, this invention is not a simple improvement on adhesives or wear-resistant coatings, nor is it a post-lamination process for prefabricated functional films. Instead, it represents a novel process path that simultaneously molds the functional layer and the polysiloxane foam matrix, achieving bulk integration through a unified cross-linking network. This technology eliminates secondary interfaces at the source, significantly solving technical problems inherent in traditional step-by-step processing, such as weak interfacial bonding, poor environmental aging resistance, cumbersome processes, and low functional integration. It provides a high-performance, highly reliable, and highly efficient method for preparing polysiloxane foam composite materials. This material is particularly suitable for cushioning, shock absorption, sealing, and structural support applications within precision electronic products such as smartphones, tablets, and wearable devices.

[0076] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. An integrated preparation method for a bifunctional surface-layer polysiloxane foam composite material, characterized in that, Includes the following steps: (1) Preparation of upper transfer film: A wear-resistant coating composition is coated on a first substrate and then cured at 120-150 °C for 30-180 seconds to obtain a surface-dried wear-resistant coating. The wear-resistant coating composition includes 5-60 parts of acrylate-modified MQ silicone resin, 10-30 parts of vinyl-terminated linear polysiloxane, 2-10 parts of hydrogen-containing crosslinking agent, 5-30 parts of inorganic wear-resistant filler, 1-10 parts of silane coupling agent, 80-120 parts of first diluent, 0.2-2 parts of adhesion promoter, 0.5-2 parts of platinum catalyst and 0.5-2 parts of inhibitor; the surface of the surface-dried wear-resistant coating still retains unreacted vinyl active groups. (2) Preparation of the lower release film: A base coating is applied to one side of the PET substrate, and a pressure-sensitive adhesive layer is applied to the other side; the base coating contains 5-15 parts of silane coupling agent, 10-25 parts of MQ resin, 1-3 parts of zinc stearate, 0.1-0.5 parts of platinum catalyst, 0.1-0.5 parts of inhibitor and 40-80 parts of ethanol, which are used to enhance the interfacial bonding between the polysiloxane foam layer and the PET substrate; (3) Preparation of foamed mixture: Mix component A and component B at a mass ratio of 1:1 to obtain foamed mixture. Component A includes vinyl-terminated linear polysiloxane, platinum catalyst, second diluent and reinforcing filler; component B includes branched polysiloxane, polysiloxane resin, hydrogen-containing crosslinking agent, inhibitor and foaming agent. (4) Mix and apply the foaming material of components A and B to the surface of the base coating, then cover the wear-resistant coating side of the upper transfer film onto the foaming mixture, and heat-cur it at 100-130 ℃ for 8-15 minutes. The foaming mixture cross-links and foams to form a polysiloxane foam matrix. At the same time, the wear-resistant coating, the polysiloxane foam matrix, and the base coating are integrated by in-situ chemical bonding. (5) Peel off the first substrate to transfer the wear-resistant coating to the polysiloxane foam matrix, and then perform secondary vulcanization at 140-200 °C for 10-30 minutes to obtain the composite material.

2. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 1, characterized in that, Component A comprises 50-80 parts of vinyl-terminated linear polysiloxane, 0.1-1.0 parts of platinum catalyst, 5-20 parts of second diluent, and 10-40 parts of reinforcing filler; Component B comprises 20-60 parts of branched polysiloxane, 20-60 parts of polysiloxane resin, 1.0-2.6 parts of hydrogen-containing crosslinking agent, 0.1-1.0 parts of inhibitor, and 1-10 parts of foaming agent.

3. The integrated preparation method of a bifunctional surface layer polysiloxane foam composite material according to claim 2, characterized in that, The vinyl-terminated linear polysiloxane has a molecular weight of 50,000 to 250,000 and a vinyl content of 0.05 to 0.30 mol.

4. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 2, characterized in that, The branched polysiloxane in component B has the following general formula: (R3) 1 SiO 1 / 2 ) a (R2 2 SiO 2 / 2 ) b (R1 3 SiO 3 / 2 ) c (SiO 4 / 2 ) d , where R 1-3 It is a C1-C6 alkyl, vinyl, or aryl group, and the molecule contains at least two vinyl groups, a+b+c+d=1, and c>0.

05.

5. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 2, characterized in that, The polysiloxane resin in component B is an organopolysiloxane resin containing M, T, and Q structural units; its weight-average molecular weight is 5000 to 50000.

6. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 2, characterized in that, The foaming agent is selected from at least one of sodium bicarbonate, low-temperature activated azodicarbonamide, or sulfonyl hydrazine.

7. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 1, characterized in that, The interfacial release force between the wear-resistant coating and the first substrate is 40-300 g / 25 mm.

8. The integrated preparation method of a bifunctional surface polysiloxane foam composite material according to claim 1, characterized in that, The first diluent and the second diluent are at least one of low-viscosity linear polydimethylsiloxane, toluene, xylene, ethyl acetate, and isopropanol.

9. An application of a bifunctional surface polysiloxane foam composite material prepared by the integrated preparation method according to any one of claims 1 to 8, used as a buffer, shock absorber or sealing component inside electronic devices.

Citation Information

Patent Citations

  • Removable pressure-sensitive adhesive composition and pressure-sensitive adhesive product

    CN106701011A

  • Foamed sponge organic silicon synthetic leather and preparation method thereof

    CN120989918A